Identifikasi Jenis Tanah Wilayah Dekat Pantai Puger Menggunakan Bagan Klasifikasi Tanah Robertson 1990.: Identifikasi Jenis Tanah Wilayah Dekat Pantai Puger Menggunakan Bagan Klasifikasi Tanah Robertson 1990. - Arief Alihudien; Priyono, Pujo (Universitas Muhammadiyah Jember, 2023)
To obtain information on soil characteristics and behavior to the foundation structure can be started by knowing the type of soil. Identifying the soil type depends on the sampling technique. It is easy if the sampling uses bore hole test, because the sample can be taken to the laboratory and then tested using a hydrometer and mechanical sieve to obtain the soil type. hydrometer and mechanical sieve to get the soil type. When using the CPT test, we generally do not get samples that can be tested in the laboratory. in the laboratory. Robertson 1986 has created a soil classification system based on the CPT test, based on the values of conus resistance qc and friction ratio fr. In this article this article, the results of the identification of common soil types in the area of near the coast of Puger Jember, in order to predict its soil behavior. The method used is by conducting CPT test for 13 points in the area. Based on the results CPT data processing, it can be seen geologically that the soil in the Puger sub-district area, especially the coastal area, on average is a sandy soil with the characteristics of silt. with the characteristics of sandy silt to sand. With this type of soil, it can be illustrated that there is potential for liquefaction in the area. in the area.